(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1999)
Cyclostratigraphy based on the quantitative analyses of planktonic foraminifera in the Zanclean segment (M Pl 1 base of M Pl 3 biozones) of the bore-hole drilled in the Capo Rossello area (Sicily, Southern Italy) allows us to recognize that the calcareous plankton biostratigraphic events occur in the same cycles as identified by previous authors. Exceptional thick cycles which are thought to represent two precession cycles show two fluctuations is greater than the number of lithologic cycles. Between the base of the Pliocene and the first occurrence of Globorotalia puncticulata thirty-five lithologic cycles and thirty eight planktonic foraminifera fluctuations are present. By comparison with relative abundance fluctuations in the benthic foraminifera and the astronomical record is recognized. In particular, the BN>125 µm and the Planulina ariminensis quantitative distributions are related to the long eccentricity. Conversely, the relative abundance fluctuations of Siphonina reticulata, Cibicidoides bradyi, Pullenia bulloides and Uvigerina pygmaea appear to be generally forced by the precession periodicity, but in the intervals coincident with the eccentricity minima such a relationship is less clear. The very abundant and widespread distribution in several Mediterranean sites of S. reticulata, which we consider a quasi-endemic species of this basin during the Early and Middle Pliocene is anticovariant with the quantitative distribution of Cibicidoides brady-robertsonianus, which is considered a characteristic species of the North Atlantic Deep Water (NADW). This relationship suggest that a peculiar, intermediate water mass was present in the Mediterranean during this time interval. We propose for this water mass the name of Early Pliocene Mediterranenan Intermediate Water (EPMIW). According to bibliographic data that report the sharp decrease in abundance of S. reticulata during the M Pl 5 biozone, EPMIW was present in the Mediterranean basin until about 2.5 Ma.